1985
DOI: 10.1103/physrevlett.55.1464
|View full text |Cite
|
Sign up to set email alerts
|

Optical Studies of Nitrogen to 130 GPa

Abstract: Nitrogen is observed to remain a molecular solid up to 130 GPa, contrary to recent theoretical predictions of metallization below 100 GPa. Raman scattering reveals three new phases at 20, 66, and 100 GPa, which are distinguished by branching of existing vibronic modes. One mode increases in frequency to a broad maximum at 66 GPa and then decreases, similar to the case of H 2 . In H2, such behavior was attributed to a weakening of the H-H bond. In N2, three other vibronic frequencies continue to increase, showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
76
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 9 publications
10
76
2
Order By: Relevance
“…At low T, nitrogen forms a molecular solid that undergoes a series of solid phase transitions with increasing pressure (see Fig. 1), which have been identified by a number of static compression experiments [10][11][12][13][14][15] . Around 50-70 GPa, density functional molecular dynamics (DFT-MD) simulations first predicted [16][17][18][19][20][21] the triple bond would destabilize to form various lower-energy, nonmolecular (possibly amorphous), polymeric phases composed of doubleor single-bonded atoms, such as cubic gauche 18 .…”
Section: Introductionmentioning
confidence: 99%
“…At low T, nitrogen forms a molecular solid that undergoes a series of solid phase transitions with increasing pressure (see Fig. 1), which have been identified by a number of static compression experiments [10][11][12][13][14][15] . Around 50-70 GPa, density functional molecular dynamics (DFT-MD) simulations first predicted [16][17][18][19][20][21] the triple bond would destabilize to form various lower-energy, nonmolecular (possibly amorphous), polymeric phases composed of doubleor single-bonded atoms, such as cubic gauche 18 .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for further pressure-induced transformations of the high-pressure molecular ζ phase but the products are believed to be closely related. 15,25 Dotted line is extrapolation of the ζ-η transformation boundary.…”
mentioning
confidence: 99%
“…This is due to different structures of both phases. As also indicated in previous Raman studies, 9,23,24 some of the intramolecular vibrations soften when the pressure increases, which can be related to the weakening of intramolecular bonding or to the increase in vibrational coupling. 25 It has been indicated that there is a more pronounced Raman and IR softening of the vibron bands of θ nitrogen as compared to the i nitrogen.…”
Section: Discussionmentioning
confidence: 80%
“…Also, by Raman spectroscopy the P -T phase diagrams of solid N 2 have been determined. 8,9,[14][15][16][17] Far-infrared study on the α-N 2 , 18 X-ray measurements for the δ phase, 6,14 the Raman scattering and X-ray diffraction 10,14,16 and also Brillouin scattering 15 studies on the ε-N 2 have been reported in the literature. Another phase η-N 2 has been observed by the Raman 9 and X-ray diffraction 19,20 measurements.…”
Section: Introductionmentioning
confidence: 99%